PATTERN OF ANTIBIOTIC PRESCRIPTION AMONG CHILDREN WITH UPPER RESPIRATORY TRACT INFECTION IN AN EGYPTIAN OUTPATIENT CLINIC DURING COVID-19 PANDEMIC - Abdel-Aziz, Basem Farouk; Allam , Eman Adel-Moustafa; Mohamed , Sara Zayed; Mohamed , Rwan Ahmed (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Objective:Study aimed to investigate the pattern of antibiotic prescription and assess its inappropriate use to treat children complaining of upper respiratory tract infection (URTI). A cross-sectional survey was conducted to identify the antibiotic prescribed to children aged 1 day -12 years who complained of URTI from February 2020 till March 2020. All guardians or care givers were interviewed for 10-15 minutes to fill in a predesigned interview schedule.Results: A total of 300 children participated in the study, their mean age was 5.83±3.59, 41.1% were school aged, males represented 57%, the medical causes of seeking medical advice were acute tonsillitis (67.0%), common cold (18.0%), sinusitis (14.0%), and Otitis media (3.0%). Antibiotic prescription rate of outpatient children was 83.0% (249/300), 16.5% of them received parenteral antibiotic. Most common antibiotics were amoxicillin and clavulanic (41.0), amoxicillin and fluxacillin (38.2), followed by cefotaxime (20.8).   All cases with acute tonsilitis and acute otitis media were prescribed antibiotics, while 50% of sinusitis and 55.56 with common cold received antibiotics. There was inappropriate use of antibiotic for outpatient children among 86.7%. Inappropriate antibiotic prescription for children on outpatient basis was a serious problem. Management strategy should be implemented to improve the quality of antibiotic use.